(untitled) (UUM Journal of Legal Studies, 2020)
In the past few years, there has been an increasing concern over the discrepancy of standards of the corporate governance amongst the developed and the developing countries since they affect their competitive advantages economically. In 2017, Saudi Arabia and Malaysia have amended their codes on corporate governance, in order to promote ethical behaviour, transparency, accountability and investor stewardship. In this paper, the researchers analyse the important features of these new codes of Saudi Arabia and Malaysia. They use a comparative approach to identify the advantages and limitations and also to determine areas for improvement. This paper finds that several transformations were already taking place in both jurisdictions. However, there are many areas that require continuous development, especially those related to the independence of the board, gender diversity problems, and impartiality in the decisionmaking process. The researchers suggest that many recommendations regarding the manner in which the two countries can address the loopholes and thereafter, improve their corporate governance codes in order to be on a par with international standards.